Construct Validity of Unidimensional General Self-Efficacy Using Confirmatory Factor Analysis - Santi Yudhistira; Deasyanti Deasyanti; Fellianti Muzdalifah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Self-efficacy is a specific domain which is divided into several aspects (e.g., magnitude, strength, and generality) based on Bandura’s theory. However, many researchers attempt to generalize the concept of self-efficacy to examine personal competence in a broader view. This study aims to test the validity of items on the General Self-Efficacy Scale (GSES), a measuring instrument that was developed by Ralf Schwarzer and designed by Matthias Jerusalem in 1979 to regulate the construction of self-efficacy as a broader concept of personality. This research used the Confirmatory Factor Analysis (CFA) method on 643 students in the Jabodetabek area to test the instrument’s validity and the CFA test results showed that out of the 10 items tested, the written statement is valid to measure the General Self-Efficacy variable.